2016
DOI: 10.18203/2349-3291.ijcp20164603
|View full text |Cite
|
Sign up to set email alerts
|

Study of risk factors of neonatal thrombocytopenia

Abstract: Background: Neonatal thrombocytopenia (platelet count < 1.5 lac/µl) is the commonest haematological abnormality encountered in neonatal intensive care unit (NICU). Thrombocytopenia if not detected can result in devastating complications. Determining the risk factors of thrombocytopenia enables us to prevent the inevitable and irreversible complications. The present study highlights the pattern, severity and risk factors of neonatal thrombocytopenia in our hospital.Methods: Prospective observational study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 13 publications
9
21
1
Order By: Relevance
“…This finding was comparable with the study done by Keerthi Tirupathi who found that 5% of the babies were associated with Meconium aspiration syndrome. 9 In the present study, out of 60 babies admitted with thrombocytopenia, Necrotising enterocolitis was seen in 5% cases. This finding was comparable with the studies done by Ramesh Babu, Lea Bonifacio, and Basil M Hanoudi, who found NEC in 4%,7%, and 4.21% respectively.…”
Section: Totalsupporting
confidence: 45%
See 3 more Smart Citations
“…This finding was comparable with the study done by Keerthi Tirupathi who found that 5% of the babies were associated with Meconium aspiration syndrome. 9 In the present study, out of 60 babies admitted with thrombocytopenia, Necrotising enterocolitis was seen in 5% cases. This finding was comparable with the studies done by Ramesh Babu, Lea Bonifacio, and Basil M Hanoudi, who found NEC in 4%,7%, and 4.21% respectively.…”
Section: Totalsupporting
confidence: 45%
“…8 Keerthi tirupathi et al, (N=200) studied about the risk factors of neonatal thrombocytopenia in 2016 at Maharashtra. 9 Ramesh babu et al, (N=100) conducted a study on the clinical profile of neonates with thrombocytopenia in 2014 at Dharmapuri. 10 Lea bonifacio et al, studied thrombocytopenia related outcome in 94 neonates in 2006 at New Jersey.…”
Section: Totalmentioning
confidence: 99%
See 2 more Smart Citations
“…The kernicterus manifests as devastating permanent brain injury leading eventually to permanent brain retardation. [3][4][5] The NH occurs because of imbalance of liver functioning due to immaturity and increased bilirubin load to detoxify. This results in lagging behind of bilirubin in capillaries giving an appearance of yellowness (jaundice).…”
Section: Introductionmentioning
confidence: 99%